2022
DOI: 10.3390/toxics10090542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure Duration and Exposure Levels of Ambient Air Pollutants on the Risk of Polycystic Ovarian Syndrome: A 2015–2019 Korean Population-Based Cohort Study

Abstract: Exposure to ambient air pollution is associated with an increased risk of menstrual disorders and infertility. This study examined the relationships between the levels and duration of air pollution exposure and the risk of polycystic ovarian syndrome (PCOS) using Korean population-based cohort data (2015–2019). Real-time data on PM10, PM2.5, O3, CO, SO2, and NO2 were provided by the Korean Ministry of Environment. The average monthly air pollutant concentration from 1 January 2014 to 31 December 2018 was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Air pollution is an increasing global problem that has been associated with a wide variety of human diseases, including PCOS (5,(29)(30)(31)(48)(49)(50). Air polution consists of a range of components including gases (SO2, NOx, NO, NO2) and suspended particulates of different sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Air pollution is an increasing global problem that has been associated with a wide variety of human diseases, including PCOS (5,(29)(30)(31)(48)(49)(50). Air polution consists of a range of components including gases (SO2, NOx, NO, NO2) and suspended particulates of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Microparticulate air pollution is believed to account for a large proportion of the public health impact of air pollution, including reproductive diseases (50,52). MAP has been associated with menstrual irregularity (53), infertility (25,30), adverse pregnancy outcomes (31), increased incidence of PCOS (5,29), and has also been linked to transgenerational transmission and infant weight gain (54,55). Human studies have shown that metabolites of tobacco (cadmium, cotine) can be found in ovarian follicular fluid and may potentially affect the developing egg (42,53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations